RECONSTRUCTING AFFECTIVE EDUCATION FOR MORAL CHARACTER FORMATION: AN EMPIRICAL STUDY OF ELEMENTARY SCHOOLS IN GARUT - Nandang Abdurohim; Mumu Abduroham; Hapid Ali (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study aimed to analyze patterns of habituation in affective education and the modeling processes used to instill moral values in developing students’ noble character at Elementary School. This research employed a qualitative case study approach. Data were collected through passive participatory observation, unstructured interviews, and documentation. Data analysis was conducted using data reduction, data display, and verification techniques, while data validity was ensured through source and technique triangulation. The results showed these practices are not entirely new, but rather represent a reconstruction of previously implemented affective education programs, which have been evaluated and refined to enhance their effectiveness. This reconstruction process involved continuous improvement based on observed outcomes, allowing schools to adjust strategies in habituation and modeling to better support students’ character development that habituation activities were systematically implemented on a daily and weekly basis, including practices such as timely worship without coercion, recitation of Asmaul Husna, congregational prayers, handshaking, and maintaining classroom cleanliness, which foster students’ awareness of religious obligations and social responsibility; and modeling strategies are carried out through teacher-led activities such as tartil and Qur’an memorization sessions, Duha prayers, and “Clean Friday” programs, which contribute to the development of students’ discipline in worship and moral behavior both in school and in the community. The implications of this study indicated that the integration of habituation and modeling strategies in affective education plays a significant role in strengthening students’ moral character.